EXERCISE THERAPY TO REDUCE COMPLAINTS IN OSTEOARTHRITIS PATIENTS - CASE REPORT - Subiyakto, Budiyatmo Joko; Widodo, Agus; Dewanti, Feryda Triana (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Osteoarthiritis (OA) is a disease joint degenerative whichinvolve the joints securingloads such as hip, knee and ankle foot. Osteoarthiritis occurs when there is abnormality radiography form the osteophytes, degree of sclerosis bone subchondral, loss of bone cartilage andsand formation ofcysts. Generally clinical symptoms of OA among others pain, stiffness and l imitation of motion. Other risk factors for knee OA are gender, obesity, joint injury, repetitive joint loading, osteoporosis and muscle weakness. Case Presentation: In this research, the method used is case report. The case report comes from a 70-year-old Mrs. S patient at one of the hospitals in Magetan.The patient complained of pain in both knees, then the right knee was more painful than the left. Knee pain experienced by the patient or less since one year ago with no known cause. The pain gets worse when you sit for a long time and when you get up from sitting to standing. Management and Outcome:The provision of isometric exercise and strengthening exercise is one of the exercise therapy that can be given to OA patients to reduce pain and increase muscle strength. Discussion:Isometric exercise is given to patients because this exercise can reduce pain because when trained isometrically the muscle contracts/moves without lengthening the muscle because no change can minimize movement and reduce pain, besides that isometric exercise uses adaptive concepts to relieve the pain felt. Strengthening exercise is given to muscles that experience weakness. Strengthening exercise can increase the resistance and stability of the knee joint so that the load received by the joint decreases. By decreasing the joint load, the pain will decrease so that functional activity will also increase Conclusion:Handling physiotherapy in the form of giving exercise therapy can reduce pain complaints in cases of osteoarthritis.